Qualitative research for education : an introduction to theories and methods - Bogdan, Robert; Biklen, Sari Knopp (Boston, Massachusetts : Allyn and Bacon Inc., 2003)
Provides readers with the necessary background information needed for understanding the uses of qualitative research in education. This new edition places qualitative research within current debates about research methods and alternative ways of knowing.
1. Foundations of qualitative research for education: an introduction -- 2. Research design -- 3. Fieldwork -- 4. Qualitative data -- 5. Data analysis and interpretation -- 6. Writing it up -- 7. Applied qualitative research for education.
Includes bibliographical references and index.
Keywords: EDUCATIONAL RESEARCH